Perceptions Of A Master Of Science Degree In Agricultural Communication By Agricultural communicators In Education (ACE): A National Study - Colleen Wilson; Curtis E. Paulson; Janet L Henderson (Journal of Applied Communications, 1991)
A sample of 254 ACE members was surveyed to determine the components of a Master of Science degree in Agricultural Communication.